Cranial Indicators Identified for Peak Incidence of Otitis Media. Issue 10 (3rd July 2017) - Pagano, Anthony S.; Wang, Eugene; Yuan, Derek; Fischer, Daniel; Bluestone, Charles; Marquez, Samuel; Laitman, Jeffrey
ABSTRACT: Acute otitis media (AOM) is one of the most common pediatric conditions worldwide. Peak age of occurrence for AOM has been identified within the first postnatal year and it remains frequent until approximately six postnatal years. Morphological differences between adults and infants in the cartilaginous Eustachian tube (CET) and associated structures may be responsible for development of this disease yet few have investigated normal growth trajectories. We tested hypotheses on coincidence of skeletal growth changes and known ages of peak AOM occurrence. Growth was divided into five dental eruption stages ranging from edentulous neonates (Stage 1) to adults with erupted third maxillary molars (Stage 5). A total of 32 three‐dimensional landmarks were used and Generalized Procrustes Analysis was performed. Next, we performed principal components analysis and calculated univariate measures. It was found that growth change in Stage 1 was the most rapid and comprised the largest amount of overall growth in upper respiratory tract proportions (where time is represented by the natural logarithmic transformation of centroid size). The analysis of univariate measures showed that Stage 1 humans did indeed possess the relatively shortest and most horizontally oriented CET's with the greatest amount of growth change occurring at the transition to Stage 2 (eruption of deciduous dentition at five postnatal months, commencing peak AOM incidence) and ceasing by Stage 3 (approximately six postnatal years). Skeletal indicators appear related to peak ages of AOM incidence and may contribute to understanding of a nearly ubiquitous human disease. Anat Rec, 2017. © 2017 Wiley Periodicals, Inc. Anat Rec, 300:1721–1740, 2017. © 2017 Wiley Periodicals, Inc.